Poverty and Social Exclusion in India : Dalits - Das, Maitreyi Bordia; Mehta, Soumya Kapoor (World Bank, Washington, DC, 2017)
This brief is based on a Poverty and Social Exclusion in India.Caste is perhaps the oldest form of social stratificationin India.After independence, the Indian Constitution abolisheduntouchability and the erstwhile untouchablescame to be known as the Scheduled Castes(SCs).The situation of Dalits has undergone dramatic transformation over time.While caste has had significant implications for poverty and other welfare outcomes, this note focuseson two arenas—education and the labor market.Our analysis based on the National Sample Survey(NSS) data suggests that there has been expansion in education among Dalits, but not at the samepace as among the upper castes.Micro studies continue to document discrimination against SC students. In the labor market, Dalits remain largely in casuallabor. Education is considered a panacea to poor labor market outcomes and overall it has positive effects for all men.It would nevertheless be naïve to dismiss the changes in caste dynamics, more so over the past two decades. Attendant to the economic changes, social movements asserting the power of Dalits have swept some states and have given Dalits a sense of political voice and agency. In sum, we find that despite localized changes,there have been modest changes for Dalits in the aggregate.